Indonesian Character Building Strategy: Planning the Pancasila Student Profile Strengthening Project in Kurikulum Merdeka - Nurdyansyah, Fafa; Muflihati, Iffah; Muliani Dwi Ujianti, Rizky; Novita, Mega; Kusumo, Haryo; ., Mujiono; Charles Ryan, John (KnE Social Sciences, 2022)
The Pancasila Student Profile Strengthening Project, or P5, is a cross-discipline project based on problems in the education sector. Since the 2021/2022 academic year, there have been 4 themes for early childhood education (Pendidikan Anak Usia Dini or PAUD), and 7 themes for elementary schools (Sekolah Dasar or SD), middle schools (Sekolah Menengah Pertama or SMP), and high schools (Sekolah Menengah Atas or SMA). The P5 makes up around 20-30% of the total credits in a year. However, teachers tend to work individually instead of collaborating with others. Therefore, this paper aims to provide guidelines on arranging the cross-discipline project so that the P5’s full potential can be realized. A systematic review was carried out on the relevant P5 databases from the perspective of the Kurikulum Merdeka. There is substantial evidence to suggest that forming a small group of teachers with a coordinator and facilitator is important. They will be responsible for planning, implementing, and evaluating the P5. This systematic review has the potential to become an important reference to build Pancasila’s character. Keywords: Kurikulum Merdeka; Merdeka Belajar; Curriculum; Pancasila; P5; Collaboration